Pembagian Harta Waris Adat Lampung Sai Batin Kabupaten Pesisir Barat Perspektif Hukum Islam - Kusnadi, Kusnadi (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2017)
This article discusses the analysis of Islamic law against the distribution of the community's heirs in Sai Batin Marga Pasar Krui. The system used by the native people in Sai Batin Pesisir Barat is divided into two forms: first, the native peoples in Pasar Krui use the matriarchal major division system. Women are only entitled to live in the house and manage the garden, but not to sell it. If they do not have a daughter, the boy is also allowed to get the heirs. Second, the native peoples in Way Napal use the patrilineal division system. The absolute decision is possessed by the heirs as the owner and the absolute decision-maker. To whom the treasure will be distributed and the amount of it is determined by the decision of the testator. The way used in this distribution is washiyah (will). This is because they are still hard with the customary rules and their lack of understanding of the Islamic inheritance law that part of Islamic religious rules.